(untitled) (Annals of Bangladesh Agriculture, 2022)
Rapid industrialization contributes to the rising economic growth rate in Bangladesh. Gazipur district is one of the largest industrial zones in Bangladesh. Every day a huge amount of untreated industrial effluents is produced and delivered to the nearby crop field or water body. These effluents might have influenced the major chemical properties of soils. Hence, the present study was conducted to assess the impact of untreated industrial effluents on soil chemical properties expressed through a spatial distribution pattern map of the industrial zone of Gazipur district. A total of one hundred and four agricultural soil samples were collected with grid basis from different unions of the industrial areas of Sreepur and Gazipur Sadar upazilas. In Sreepur upazila, the mean values of soil pH, organic carbon (OC), N, P, S, K, Ca and Mg were 4.85, 0.81%, 0.11%, 6.08 ppm, 26.5 ppm, 0.13 meq/100g soil, 0.53 meq/100g soil and 0.19 meq/100g soil, respectively in uncontaminated soil, while the mean values of soil pH, OC, N, P, S, K, Ca and Mg were 5.15, 1.96%, 0.23%, 14.2 ppm, 187.61 ppm, 0.15 meq/100g soil, 0.64 meq/100g soil and 0.2 meq/100g soil, respectively due to industrial contamination. In both the upazilas, soil pH was strongly to slightly acidic while soil organic carbon was low to medium and N content was low. A weak spatial variation was detected for soil pH and N in these industrial areas indicating less influence on both the parameters by the effluents. Similarly, the contents of K, Ca and Mg were low in most of the areas of these two upazilas and a very little or no spatial variation was observed. On the other hand, OC and P contents were low to medium whereas S content was high in most of the study areas. Ann. Bangladesh Agric. (2022) 26 (1) : 15-28